Criminal Prosecution Against the Crime of Legal Entities in Vietnam - Phuong, Do Thi (VNU Journal of Science: Legal Studies; Vol 39 No 1DO - 10.25073/2588-1167/vnuls.4365, 2023)
In this article we focus on the study of the current state of criminal law and criminal procedure in Vietnam on criminal prosecution of legal entities in order to find out the problems, thus proposing to ensure the effective implementation of criminal prosecution of legal entities in Vietnam. In order to solve these problems, we will compare the laws of Vietnam with the legal regulations of some countries in the world on the criminal liability of legal entities and analyze the current situation of Vietnamese law to indicate the incompatibility with the laws of other countries and their inadequacies, problems, and feasibility. Accordingly, we will make recommendations to amend and supplement some provisions of Vietnamese law on criminal prosecution of legal entities and recommend measures to ensure the implementation of the rules. This is in fact a fast, accurate, and relevant context of globalization today in Vietnam.